The Influence of Educational Diversity on Shareholder Value Creation in South African Corporate Boards - Zvinowanda, Douglas; Mafini, Chengedzai; Beneke, John D. (International Journal of Economics and Financial Issues, 2024)
This study investigates the influence of board education diversity on shareholder value creation of South African non-financial companies listed on the JSE for the 10 years from 2013 until 2022. In this study, a quantitative quasi-experimental design was used. Data were collected from 2013 to 2022 from 101 non-financial companies listed on the JSE. The final sample consisted of 1010 company-year observations. The study measured board education level diversity using the proportion of board members with master’s degrees, the proportion of board members with PhD and the Blau index for board education level diversity. On the other hand, the proxies of shareholder value creation included the standardised market value added, market-to-book ratio and Tobin’s Q. A fixed effects panel data regression model was employed to estimate the influence of board members’ education diversity measures on shareholder value creation measures. Based on linear models, the proportion of board members with master’s degrees and the proportion of board members with PhDs negatively influence all shareholder value creation measures. In contrast, BI_BED positively impacts all shareholder value creation measures. Concerning curvilinear quadratic models, all board members’ education diversity measures positively and negatively impact all shareholder value creation measures, highlighting an inverted U-shaped effect. This study advances the understanding of the double-edged sword effect of educational diversity on shareholder value creation in South African corporate boards.